1996
DOI: 10.1002/art.1780390318
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐10 inhibition of the progression of established collagen‐induced arthritis

Abstract: Objective. Interleukin-10 (IL-10) is a potent inhibitor of the proinflammatory cytokines, including tumor necrosis factor a and IL-1, which are considered important in the pathogenesis of rheumatoid arthritis (RA). The study was undertaken to establish whether IL-10 can ameliorate arthritis in the collagen-induced arthritis (CIA) model of RA.Methods. DBM1 mice were immunized with bovine type I1 collagen in adjuvant, and treated daily after disease onset with recombinant murine IL-10 or with saline as a control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
153
1

Year Published

1998
1998
2010
2010

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 246 publications
(168 citation statements)
references
References 46 publications
14
153
1
Order By: Relevance
“…Intraarticular administration of IL-10 did not reduce the severity of arthritis (34), whereas systemic injection with recombinant IL-10 effectively inhibited disease (36). We detected a higher proportion of IL-10-producing T cells in the spleen after tolerogenic DC treatment, suggesting a systemic increase in IL-10.…”
Section: Discussionmentioning
confidence: 66%
“…Intraarticular administration of IL-10 did not reduce the severity of arthritis (34), whereas systemic injection with recombinant IL-10 effectively inhibited disease (36). We detected a higher proportion of IL-10-producing T cells in the spleen after tolerogenic DC treatment, suggesting a systemic increase in IL-10.…”
Section: Discussionmentioning
confidence: 66%
“…However, these studies showed different results regarding humoral immune responses to collagen type II (CII). In our laboratory no significant differences in the Ab profile between controls and IL-10-injected animals has been observed over the 10-day treatment period (7). On the contrary, other investigators found a reduction of autoantibodies to CII in rat collagen-induced arthritis (CIA) when IL-10 was administered systemically and an increase when it was injected locally in the paws (8).…”
mentioning
confidence: 61%
“…In many cases, their precise roles are, as yet, incompletely defined. A growing body of evidence from both animal models of arthritis and human RA suggests that Th2-type cytokines, such as IL-4 and IL-10, can protect against arthritis, whereas Th1-type cytokines, such as IL-2 and IFN-␥, can be pro-inflammatory (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12).…”
Section: Heterogeneous Effects Of Il-2 Onmentioning
confidence: 99%